Oxidative stress features in patients with combined course of type 2 diabetes mellitus and osteoporosis residing in anthropogenic pressure conditions - Kryvenko, V. I.; Borodavko, O. I. (Zaporozhye Medical Journal, 2019)
The purpose of the study is to compare indicators of oxidative stress (OS) and bone mineral density in patients with combined course of type 2 diabetes mellitus (DM) and osteoporosis (OP), who are permanently resident in industrial regions and in environmentally friendly conditions. Materials and methods. A total of 74 patients with combined course of type 2 DM and OP have been examined. The main group included 50 patients who had permanent residence in Zaporizhzhia city (industrial region). The comparison group included 24 patients with combined course of type 2 DM and OP who were born and lived in Mykhailivka town of the Zaporizhzhia region (ecological region). All the patients underwent ultrasound densitometry using the Omnisense 7000 ultrasound densitometer (Beam Medical Ltd,Israel). Osteoporosis risk index (ORI) was calculated for each patient as an average index for 2 bones. The OS intensity was assessed by nitrotyrosine and 8-hydroxyguanine serum levels. Serum glucose and glycosylated hemoglobin (HbA1c) were also measured. Results. The main group patients did not significantly differ from the comparison group patients in terms of OP risk factors, age, gender, duration and course of type 2 DM. The mean values of nitrotyrosine and 8-hydroxyguanine levels were significantly 2.5 times (P < 0.05) and 1.4 times (P < 0.05) higher, respectively, in the main group as compared to similar patients from the environmentally friendly region. The bone mineral density in the industrial region group was significantly lower. Thus, the Rad-Tib ORI was 12 % higher in the main group, Rad-Ph ORI – by 19 %, and Tib-Ph ORI – by 16 % compared with the comparison group (P < 0.05). Conclusions. The processes of OS are intensified and severity of osteoporosis is increased in the patients with combined course of type 2 diabetes mellitus and OP who have been permanently living in the large industrial city compared to the residents of the environmentally friendly region.